Social Studies Learning Innovation Using Deep Learning And Gamification ZEP Quiz - Dina Siti Logayah; Sapriya; Retno Ayu Hardiyanti; Sopi Sopianti Nur Irvan (Universitas Negeri Yogyakarta, 2026)
Background: The digital era demands adaptive and innovative social studies education to move beyond conventional teacher-centered approaches that rely on memorization Objectives: This Community Service (PkM) activity aims to strengthen the capacity of social studies teachers in developing learning evaluation models based on deep learning and gamification using the ZEP Quiz platform. Method: The activity utilized a hands-on, participatory workshop method combined with a reflective mentoring approach, involving 134 social studies teachers from the MGMP IPS Bandung City. The procedure followed four systematic stages: preparation, implementation, evaluation, and follow-up. Result: Statistical analysis using the Wilcoxon Signed Rank Test showed a significant increase in teachers' understanding of deep learning concepts and digital pedagogical skills (p < 0.05). Teacher confidence in utilizing digital media rose significantly from 38% to 87% post-training. Furthermore, the workshop successfully produced 80 interactive quiz products ready for classroom implementation. Conclusion: This activity successfully achieved its targets by improving teacher professionalism, fostering a collaborative digital culture through the MGMP network, and encouraging sustainable innovation in technology-based social studies learning. Despite minor technical and time constraints, the program proves effective as a model for teacher professional development in the 21st century.